Biology, ecology and management of the south american tomato pinworm, tuta absoluta - Urbaneja, Alberto; Desneux, Nicolas; Gabarra, Rosa; Arnó, Jaume; González-Cabrera, Joel; Mafra-Neto, A.; Stoltman, L.; De Sene Pinto, A.; Parra, J. R. P. (2017)
This chapter focuses on the South American tomato pinworm Tuta absoluta (I) origin, spread and current distribution; (II) basic but critical information regarding bioecology; (III) rearing techniques; (IV) known host plants; (V) sampling and monitoring techniques; and (VI) control methods available from both South America and newly infested areas, as well as their potential use for integrated pest management. Some hints are provided on present and future management strategies.